2020
DOI: 10.1155/2020/8884133
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Evaluation of Reinforced Concrete Columns Retrofitted with FRP for Blast Mitigation

Abstract: Fiber reinforced polymer (FRP) material is commonly applied in retrofitting structures due to the advantages of high strength and well corrosion resistance. Previous studies indicated that retrofitting with FRP sheet was an effective way for protecting the existing structures to resist the blast loads, but little research made comprehensive comparison study on the blast response of RC columns with different retrofitting strategies. This paper proposed a series of FRP retrofitting strategies and evaluated their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
(34 reference statements)
0
2
0
Order By: Relevance
“…FEA simulations revealed a result that CFRP strengthening could be an optimal and effective solution to mitigate the damage associated by the blast induced shock waves. Moreover, Zhang et al [21] and Zhao et al [22] conducted a numerical investigation on methods of enhancing capacity of RC column. Zhang et al [21] performed a novel work to determine the effect of axial compression ratio, torsional-bending ratio, and eccentricity on the load carrying capacity of RC column strengthened by high performance ferrocement Laminate (HPFL)-bonded steel plates (BSP) prone to combined loading cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FEA simulations revealed a result that CFRP strengthening could be an optimal and effective solution to mitigate the damage associated by the blast induced shock waves. Moreover, Zhang et al [21] and Zhao et al [22] conducted a numerical investigation on methods of enhancing capacity of RC column. Zhang et al [21] performed a novel work to determine the effect of axial compression ratio, torsional-bending ratio, and eccentricity on the load carrying capacity of RC column strengthened by high performance ferrocement Laminate (HPFL)-bonded steel plates (BSP) prone to combined loading cases.…”
Section: Introductionmentioning
confidence: 99%
“…The authors reported, all damage strengthened specimens under combined loading cases exhibited increase in load carrying capacity of specimen whereas energy absorption capacity and ductility ratios were reduced significantly. Zhao et al [22] developed a numerical model to investigate the behavior of RC columns retrofitted with various FRPs composites such as CFRP, GFRP, and AFRP as external jacketing material for RC columns under blast loads. The authors reported among the three FRP types, CFRP performed well in enhancing blast resistance capacity of RC column.…”
Section: Introductionmentioning
confidence: 99%